Designing a Modern Web Interface with Vue.js and Tailwind for University Information System - Perdana, Fhadiel Putra; Supratman, Edi; Saputra, Dhimas Rosanto (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The development of responsive, efficient, and maintainable web applications is a critical challenge in modern web development. This study presents the design and development of a tracer study information system for Bina Darma University using Vue.js and Tailwind CSS. The system focuses on three key components: responsive web design, pagination for managing large datasets, and reusable components implemented with Vue.js slots. By integrating Tailwind CSS, the system achieves a highly adaptive interface optimized for various devices, ensuring a seamless user experience. The implementation of Vue.js-based pagination significantly improves the management of alumni questionnaire histories in the admin interface, enhancing navigation and performance. Additionally, the use of Django pagination complements this by efficiently handling server-side data management, allowing for smooth transitions between pages and reducing load times for large datasets. This dual approach to pagination ensures that both client-side and server-side data handling are optimized for performance. Furthermore, the use of Vue.js slots for component reuse allows for tailored functionalities across different interfaces, reducing redundancy and improving code maintainability. The results demonstrate that adopting modern frameworks like Vue.js and Tailwind CSS, alongside robust backend solutions like Django, can streamline development, reduce effort, and enhance application efficiency. This study provides a scalable solution that can be adapted for similar academic systems, offering insights into best practices for contemporary web application development.